Alginate Gel Immobilization of Caenorhabditis elegans for Optical Calcium Imaging of Neurons - Mangalath, Aswathy; Raj, Vishnu; Santhosh, Rasitha; Thekkuveettil, Anoopkumar (Bio-protocol, 2023)
A fascinating question in neuroscience is how sensory stimuli evoke calcium dynamics in neurons. is one of the most suitable models for optically recording high-throughput calcium spikes at single-cell resolution. However, calcium imaging in is challenging due to the difficulties associated with immobilizing the organism. Currently, methods for immobilizing worms include entrapment in a microfluidic channel, anesthesia, or adhesion to a glass slide. We have developed a new method to immobilize worms by trapping them in sodium alginate gel. The sodium alginate solution (5%), polymerized with divalent ions, effectively immobilizes worms in the gel. This technique is especially useful for imaging neuronal calcium dynamics during olfactory stimulation. The highly porous and transparent nature of alginate gel allows the optical recording of cellular calcium oscillations in neurons when briefly exposed to odor stimulation.